Analysis of free-throw quotas of left-handed and right-handed elite basketball players - Papadopoulos, P.; Lindner, M.; Ergec, D.; Stafilidis, S.; Goebel, R.; Baum, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Research in the domain of handedness in sports showed that a tactical advantage is attributed to left-handed athletes in many sports (Brooks et al., 2003; Wood and Aggleton, 1989). There are only a few studies which analysed performance of sport-specific motion sequences of right- (RH) and left-handed (LH) athletes (Grondin et al., 1999). The aim of this study was to examine whether LH elite basketball players have a better free throw quota than RH elite basketball players. Methods: The free throw performance of 299 players who participated in the season 2006/2007 of the NBA was evaluated statistically. The data were taken from the NBA website. The players were classified depending on position and handedness (right-hander: n=280, left-hander: n=19). The handedness was identified using the official list of LH players of the Association for Professional Basketball Research. In addition an online search of photos of all players was made. In order to discover significant differences between the free throw quota of all LH and RH basketball players and those playing the same position the Mann-Whitney-U-test was used. Results: The free throw quota of the LH players was significantly higher (p= 0.034*). The highest significant result (p= 0.011*) was shown on the guard position. For the forward and center position no significant difference respectively no representative finding was obtained. There were over two times more LH players (26.3%) than RH players (12.1%) reaching a free throw quota over 85%. On the other hand, almost two times more RH players (19.3%) than LH players (10.5%) were found reaching a free throw quota under 65% Discussion: In contrast to other studies the strategic advantages, which were considered to be the reason for the superior performance of left-handers, are excluded in the free throw situation. The better performance of left-handers has been attributed to neurological benefits (Anzola et al., 1977; Geschwind and Galaburda, 1985). These benefits are often associated with better visual and spatial abilities (Nass and Gazzaniga, 1987) and could explain the results of this study and the findings of other examinations (Dane and Erzurumluoglu, 2003; Stöckel et al., 2007). Further studies examining different motor skills, a greater number of subjects and the reasons for the phenomenon found should be conducted.